The effectiveness and predictors influencing the outcome of onabotulinumtoxinA treatment in chronic migraine: understanding from diverse patient profiles in a single session - Ilgaz Aydinlar, Elif; Erdogan Soyukibar, Tuba; Yalinay Dikmen, Pinar (Frontiers in Neurology, 2024)
Objective This real-world study aimed to investigate how onabotulinumtoxinA affects the outcome of migraine, along with accompanying anxiety, depression, and bruxism among a group of patients with chronic migraine (CM) and define predictors of good response. Methods Patients diagnosed with CM who received onabotulinumtoxinA were included in this single-center, real-world retrospective cohort study. Monthly headache days (MHDs), monthly migraine days (MMDs), headache intensity (numeric rating scale-NRS) and headache characteristics were evaluated at baseline and 12 weeks post-treatment. Patient-reported outcome measures (PROMs) included Migraine Disability Assessment Scale (MIDAS), Headache Impact Test-6 (HIT-6) scores, 12-item Allodynia Symptom Checklist (ASC-12), Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI). Response to onabotulinumtoxinA (% reduction in MHDs) and treatment-related adverse events (TRAEs) were also evaluated. OnabotulinumA was applied to the masseter muscles in patients complaining of bruxism. Results A total of 72 patients (mean ± SD age: 36.3 ± 8.5 years; 91.7% were female) diagnosed with CM were included. OnabotulinumtoxinA revealed significant decrease in median (IQR) MHDs [from 20(15–25) at baseline to 6(4–10), p < 0.001], MMDs [from 9(6–12) to 3(1–6), p < 0.001] and NRS [from 9(8–10) to 7(6–8), p < 0.001], and the MIDAS [from 54(30–81) to 16(7–24), p < 0.001], HIT-6 [from 67(65–69) to 58(54–64), p < 0.001], ASC-12 [from 6(1.5–9) to 2(0–9), p = 0.002], BAI [from 12(6.5–19) to 9(3–17), p < 0.001] and BDI [from 11(6.5–17) to 3(2–7) p < 0.001] scores at 12 weeks post-treatment. Patients complaining of bruxism received onabotulinumtoxinA injections in the first n = 27 (37.5%) and 12. week post-treatment n = 19 (70.4%) periods. Overall, 70.8% of patients responded (≥50% reduction in MHDs), while 29.2% did not (<50% reduction). Both groups showed similar characteristics in demographics, migraine history, baseline PROMs scores, comorbidities, and prior treatments. Conclusion OnabotulinumtoxinA is an effective treatment option that rapidly improves migraine outcomes, disability, and impact while also alleviating comorbid depression and/or anxiety. This study’s noteworthy finding is that onabotulinumtoxinA is effective in a majority of CM patients, irrespective of their prior treatment history, migraine characteristics, or concurrent comorbidities. Furthermore, we identified no specific predictors for a favorable response to onabotulinumtoxinA. Applying onabotulinumtoxinA to the masseter muscles can relieve discomfort associated with concurrent bruxism; however, it does not impact migraine outcomes.